Synästhesie als Diskurs: Eine Sehnsuchts- und Denkfigur zwischen Kunst, Medien und Wissenschaft - Gruß, Melanie (transcript, 2017)
A fresh look at synesthesia discourse in the sciences and humanities since the 19th century – while at the same time an interdisciplinary and original cultural history of the modern!